Effect of combined ankle exercise and self foot massage on ankle-brachial index and diabetic peripheral neuropathy symptoms - Rias, Yohanes Andy; Sofiani, Yani; Yunitri, Ninik; Rayasari, Fitrian; Hernani, Eny (Riset Informasi Kesehatan, 2024)
Background: Buerger Allen Exercise (BAE) and Self-Thai Foot Massage (STFM) are strongly recommended ameliorating Diabetes Peripheral Neuropathy (DPN) symptoms. Nevertheless, there is lack of evidence on the combination of both on alleviating DPN symptoms and Ankle-Brachial Index (ABI). Aims: This study aimed to examine the combination effect of BAE and STFM on symptoms of diabetic peripheral neuropathy and ABI among individuals with DPN. Methods: The research design used an experimental one-group with pre-test and post-test design. In total, 36 eligible individuals with DPN with a seven-day received combination of BAE and STFM implementing ankle exercise and foot massage. DPN scores were measured using the Michigan Screening Instrument (MNSI) questionnaire and foot perfusion was measured using the ABI. An analysis of the research data was conducted using the Paired t-test and effect size with Cohen’s d with a significance threshold of p >0.05. Results: There are a significant finding combination of BAE and STFM on MNSI subjective (mean diff=-2.78, p=>.001, d=0.71), MNSI objective (mean diff=-1.60, p=>.001, d=0.38), ABI left (mean diff= 0.01, p=>.001, d=0.51), and ABI right (mean diff=0.07, p=>.001, d=0.59). Conclusion: The finding of this study indicates that a combination of BAE and STFM is a feasible alternative therapy for ABI and MNSI in patients with DPN.